Problem 2-9: Differentiating Polynomial and Rational Functions

Differentiate
a)  f\left(x\right)= 1+ 2x
b)  f\left(x\right)= 1 - 2x + 2x^2
c)  f\left(x\right)= 1- x^2 +\frac{1}{x}
d)  f\left(x\right)= 1 - x +\frac{1}{1-x}

Solution
The following rules can be used:
I)  \displaystyle\frac{d}{dx}ax^n=anx^{n-1}
II)  \displaystyle\frac{d}{dx}\left(u+v\right)=\frac{du}{dx}+\frac{dv}{dx}
III)  \displaystyle\frac{d}{dx}\frac{u}{v}=\frac{1}{v^2}\left(v\frac{du}{dx}-u\frac{dv}{dx}\right)

a)  f\left(x\right)= 1+ 2x
 \displaystyle\frac{d}{dx}f\left(x\right)= \displaystyle\frac{d\left(1+2x\right)}{dx}=0+2=2

Problem 2-9-a
b)  f\left(x\right)= 1 - 2x + 2x^2
 \displaystyle\frac{d}{dx}f\left(x\right)= \displaystyle\frac{d\left(1 - 2x + 2x^2\right)}{dx}=\displaystyle\frac{d}{dx}1 + \displaystyle\frac{d}{dx}\left(- 2x\right) + \displaystyle\frac{d}{dx}\left(2x^2\right)=0-2+2\times 2 \times x^{2-1}=4x-2
Problem 2-9-b

c)  f\left(x\right)= 1- x^2 +\displaystyle\frac{1}{x}
 \displaystyle\frac{d}{dx}f\left(x\right)= \displaystyle\frac{d}{dx} \left(1- x^2 +\displaystyle\frac{1}{x}\right)=\displaystyle\frac{d}{dx} 1+ \displaystyle\frac{d}{dx} \left(- x^2\right)+\displaystyle\frac{d}{dx}\left(\displaystyle\displaystyle\frac{1}{x}\right) =0 -2x^{2-1}+\displaystyle\frac{d}{dx}x^{-1}=-2x +\left(-1\right) \times x^{-1-1}=-2x-\displaystyle\frac{1}{x^2}
Problem 2-9-c
d)  f\left(x\right)= 1 - x +\displaystyle\frac{1}{1-x}
 \displaystyle\frac{d}{dx}f\left(x\right)= \displaystyle\frac{d}{dx} \left(1 - x +\displaystyle\frac{1}{1-x}\right)= \displaystyle \frac{d}{dx} 1 + \displaystyle\frac{d}{dx} \left(- x\right) + \displaystyle\frac{d}{dx}\displaystyle\frac{1}{1-x}

Let’s use rule III to find  \frac{d}{dx}\frac{1}{1-x}.
 u=1, v=x-1, du =0, dv=dx \to \displaystyle\frac{d}{dx}\left(\displaystyle\frac{1}{x}\right)=\displaystyle\frac{d}{dx}\displaystyle\frac{u}{v}=\displaystyle\frac{1}{v^2}\left(v\displaystyle\frac{du}{dx}-u\displaystyle\frac{dv}{dx}\right)
=\displaystyle\frac{1}{\left(x-1\right)^2}\left(\left(x-1\right)\displaystyle\frac{du}{dx}-1\times \displaystyle\frac{dv}{dx}\right) = \displaystyle\frac{1}{\left(x-1\right)^2}\left(0-1\right)=\displaystyle\frac{1}{\left(x-1\right)^2}

Therefore,
 \displaystyle\frac{d}{dx}f\left(x\right)=\displaystyle\frac{d}{dx} 1 + \displaystyle\frac{d}{dx} \left(- x\right) + \displaystyle\frac{d}{dx}\displaystyle\frac{1}{1-x}=0-1+\displaystyle\frac{1}{\left(x-1\right)^2}=\displaystyle\frac{1}{\left(x-1\right)^2}-1
Problem 2-9-d

Comments

3 responses to “Problem 2-9: Differentiating Polynomial and Rational Functions”

  1. ankit negi Avatar

    It’s wery useful site for us.

  2. ankit negi Avatar

    It’s very useful wapsite for us.

  3. Normand Avatar

    Fine way of telling, and good article to get data on the topic of my presentation focus, which i am going to convey in university.

Leave a Reply

Your email address will not be published. Required fields are marked *